Analisis Pengendalian Kualitas Menggunakan Metode FTA dan FMEA Untuk Mengurangi Produk Cacat Serat Rayon di PT. XYZ - Akbar, Ali; Bintang Nidia Kusuma; Osep Hijuzaman; Sheva Parian Pushya (Jurnal Teknologika, 2025)
This research was conducted at PT. XYZ is engaged in the textile industry. The problem was experienced due to defects in the Rayon Fiber production process. The purpose of the study was to determine the Rayon Fiber production process at PT. XYZ, to determine the factors causing defects using the Fault Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA) methods, and to provide suggestions for improvement to reduce product defects. The results of the observation showed that there were three types of defects, including White Brightness, Yellow Brightness, and Damaged Wrapping. Of the three aspects, the most dominant types of defects were White Brightness, and Damaged Wrapping seen in the production process in December with a percentage of defects of 14.8%. From the Pareto diagram, it is clear that three problems cause defective goods. To reduce the number of faulty goods, the most common issues - namely, damaged wrapping and white brightness defects - must be addressed by fixing the most defective goods using the 80%/20% approach. After obtaining the severity, occurrence, and detection values related to window product defects, the RPN value will be calculated by multiplying the values above (RPN = S x O x D). By doing the repairs, it resulted in improvements marked by a decrease in the RPN value from 1290 to 553 or 42.8%. The root cause of the problem was because the operator did not follow the existing work standards and did not use the navigation system during the production process. From the results of the study, several suggestions for improvement were obtained, namely conducting periodic supervision and providing re-training to operators regarding the importance of working according to SOP.